EVALUASI KINERJA SATUAN POLISI PAMONG PRAJA (SATPOL PP) DALAM PENERTIBANPEDAGANG KELILING DI KOTA PEKANBARU TAHUN 2023 - Ketaren, Rayhan; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The issue of mobile street vendors operating on road shoulders and sidewalks in Pekanbaru City has caused disruptions to public order, traffic flow, and the overall quality of public spaces. This situation has drawn the attention of local authorities, as it violates Regional Regulation Number 13 of 2021 concerning Public Order and Community Tranquility. The Civil Service Police Unit (Satpol PP), as the law enforcement agency for local regulations, holds a strategic role in regulating the activities of these mobile vendors. However, the effectiveness of Satpol PP’s performance in carrying out this function remains in question, particularly regarding the long-term impact of the enforcement efforts. This study aims to describe the performance evaluation of Satpol PP Pekanbaru City in regulating mobile vendors in 2023. The research employed a descriptive qualitative approach, with data collected through interviews, and documentation. The findings reveal that although enforcement activities have been routinely conducted, their long-term impact remains suboptimal due to limited resources, the absence of standard operating procedures (SOP), weak deterrent effects, and the lack of alternative solutions for the vendors. Therefore, a more integrative and sustainable strategy is required to enhance the effectiveness of Satpol PP’s performance in maintaining public order in the city. Keywords: Performance Evaluation, Civil Service Police Unit, Mobile Vendors, Enforcement, Public Order.